Brugada pattern revealed during SARS-COV-2-related multi-systemic inflammatory syndrome in a 6-year-old child. Issue 2 (7th February 2022) - Picconi, Enzo; Buonsenso, Danilo; De Rosa, Gabriella; Morena, Tony Christian
Abstract : Rhythm abnormalities are rare during COVID-19-related multisystem inflammatory syndrome in children (MIS-C). We are reporting the detection of type I Brugada pattern in a 6-year-old child with MIS-C. Following the start of treatment (systemic steroids and immunoglobulins), a gradual evolution of cardiac rhythm up to normalisation was observed, concomitantly with a progressive reduction of inflammatory markers.